Highly Correlated Wiener polarity Index: A Model to Predict Log p - Immadesetty Pothu Raju (International Journal of Advances in Applied Sciences, 2014)
Wiener polarity index of a more generalized graph of chemical graphs of polyacenes and phenylenes is computed and the results are used to design a model for predicting log p values of polyacenes. The multiple regression with two descriptors gives improved models with correlation coefficient 0.999999980642502.